1996
DOI: 10.1515/hc.1996.2.4.359
|View full text |Cite
|
Sign up to set email alerts
|

A Modification to the Hantzsch Method to Obtain Pyridines in a One Pot Reaction: Use of a Bentonitic Clay in a Dry Medium

Abstract: A new synthetic method to obtain pyridines in a one pot reaction by a modification of the Häntzsch method, in a dry medium using the NH4N03/bentonite system and microwave energy is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…However, many of these methodologies have been associated with several problems such as long reaction times, expensive reagents, harsh conditions, low product yields, and occurrence of several side products. Although several reports have described the oxidative aromatization of 1,4-dihydropyridine derivatives, to the best of our knowledge, there are only a few examples on the one-pot synthesis and oxidative aromatization of Hantzsch derivatives [31,32]. For example, Cotterill et al [32] have demonstrated the applicability of the MICROCOS (Microwave-assisted Combinatorial Synthesis) technology for generating combinatorial libraries of pyridine derivatives using the Hantzsch synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…However, many of these methodologies have been associated with several problems such as long reaction times, expensive reagents, harsh conditions, low product yields, and occurrence of several side products. Although several reports have described the oxidative aromatization of 1,4-dihydropyridine derivatives, to the best of our knowledge, there are only a few examples on the one-pot synthesis and oxidative aromatization of Hantzsch derivatives [31,32]. For example, Cotterill et al [32] have demonstrated the applicability of the MICROCOS (Microwave-assisted Combinatorial Synthesis) technology for generating combinatorial libraries of pyridine derivatives using the Hantzsch synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…4-Substituted Hantzsch 1,4-dihydropyridines were synthesized by replacing ammonium acetate with ammonia in a classical method, in which the products can be subsequently oxidized to corresponding pyridines. To the best of our knowledge, only two articles reported the continuous synthesis of Hantzsch pyridines by a mixture of bentonite clay, b-ketoester, aldehyde, and ammonium nitrate as the source of ammonia and oxidizing species [22,23]. These results are intriguing as they are somehow contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…These results are intriguing as they are somehow contradictory. In one of these reports [22], in the absence of solvent, the alkylated pyridine was isolated from the oxidation of 4-isopropyl dihydropyridine as the major product. On the other hand, dealkylated pyridine was isolated from the oxidation of 4-propyl or 4-phenyl dihydropyridines in substantial yield that this…”
Section: Introductionmentioning
confidence: 99%
“…In previous papers, we described the use of a natural clay as acid catalyst in different organic reactions (3)(4)(5)(6). We present in this report the results obtained for the reaction of primary amines with acetonylacetone using infrared radiation and a natural clay as catalyst in absence of solvent, as a variation to the Paal-Knorr reaction.…”
mentioning
confidence: 95%